Truth and the new kind of Christian the emerging effects of postmodernism in the church - Smith, R. Scott, 1957- (Wheaton, IL Crossway, 2005)
Includes bibliographical references and index.
Keywords: Postmodernism -- religious aspects -- Christianity; Evangelicalism